Integração estratégica do transporte na cadeia varejista: otimização do transporte em fornecedores de componentes para a indústria de bens de consumo não duráveis - Lopes, Marco Antonio de Oliveira (2005)
This master thesis analyses the role of the logistics in the supply chain and proposes the strategic integration of the third party transportation services contracted by manufacturers of components for industries of mass consumption products for human nutrition, personal care & beauty and housecleaning. It also presents the study of the Brazilian reality regarding the cargo transportation infrastructure and process and its impact over the feasibility of large scope optimized supply chains.